Risk Factors in IT Public–Private Partnership Projects. (October 2019) - Ghribi, Souhir; Hudon, Pierre-André; Mazouz, Bachir
Project managers from both the public and private sectors have always known that better project management is often synonymous with better risk management. As such, all projects are subject to risk factors that make their management more or less complicated. In this article, we contend that successful project managers need tools to better identify and assess project risks and we try to provide such a tool in the form of grid of specific risk factors. This article analyzes risk factors in IT projects conducted using public–private partnership (PPP) procurement from the public partner's perspective. Our research uses, as empirical case studies, three projects undertaken by the Tunisian government in partnership with IT and engineering companies. The results reveal 13 specific risk factors, which are classified into three generic risk factor categories: strategic, operational, and key resources. The adverse effects of risks materializing are also identified and analyzed.